Nucleus Tractus Solitarius Neurons Activated by Hypercapnia and Hypoxia Lack Mu Opioid Receptor Expression - Maletz, Sebastian N.; Reid, Brandon T.; Varga, Adrienn G.; Levitt, Erica S. (Frontiers in Molecular Neuroscience, 2022)
Impaired chemoreflex responses are a central feature of opioid-induced respiratory depression, however, the mechanism through which mu opioid receptor agonists lead to diminished chemoreflexes is not fully understood. One brainstem structure involved in opioid-induced impairment of chemoreflexes is the nucleus of the solitary tract (NTS), which contains a population of neurons that express mu opioid receptors. Here, we tested whether NTS neurons activated during chemoreflex challenge express mu opioid receptors and overlap with neurons activated by opioids. Using genetic labeling of mu opioid receptor-expressing neurons and cFos immunohistochemistry as a proxy for neuronal activation, we examined the distribution of activated NTS neurons following hypercapnia, hypoxia and morphine administration. The main finding was that hypoxia and hypercapnia primarily activated NTS neurons that did not express mu opioid receptors. Furthermore, concurrent administration of morphine with hypercapnia induced cFos expression in non-overlapping populations of neurons. Together these results suggest an indirect effect of opioids within the NTS, which could be mediated through mu opioid receptors on afferents and/or inhibitory interneurons.